Clinical Predictors of a Low Central Venous Oxygen Saturation after Major Surgery: A Prospective Prevalence Study. Issue 1 (January 2015) - Litton, E.; Silbert, B.; Ho, K. M.
Optimising perioperative haemodynamic status may reduce postoperative complications. In this prospective prevalence study, we investigated the associations between standard haemodynamic parameters and a low central venous oxygen saturation (ScvO2 ) in patients after major surgery. A total of 201 patients requiring continuous arterial and central venous pressure monitoring after major surgery were recruited. Simultaneous arterial and central venous blood gases, haemodynamic and biochemical data and perfusion index were obtained from patients at a single time-point within 24 hours of surgery. A low ScvO2 (<70%) was observed in 109 patients (54%). Use of mechanical ventilation, mean arterial pressure, central venous pressure, haemoglobin concentrations, arterial pH and lactate concentrations, arterial oxygen (PaO2 ) and carbon dioxide tensions (PaCO2 ) were all associated with a low ScvO2 in the univariate analyses. In the multivariate analysis, only a higher perfusion index (odds ratio [OR] 0.87, 95% confidence interval [CI] 0.78 to 0.98), PaO2 (OR 0.98 per mmHg increment, 95% CI 0.97 to 0.99) and PaCO2 (OR 0.88 per mmHg increment, 95% CI 0.82 to 0.95) and a lower central venous pressure (OR 1.14 per mmHg increment, 95% CI 1.04 to 1.25) were significantly associated with a reduced risk of a low ScvO2, all in a linear fashion. In conclusion, PaO2, PaCO2, perfusion index and central venous pressure were significant predictors of a low ScvO2 in patients after major surgery including cardiac surgery, suggesting that ScvO2 should always be interpreted with the arterial blood gases and that liberal perioperative fluid therapy aiming at a high central venous pressure may be detrimental in optimising ScvO2 .